PENGARUH HARGA, CITRA MEREK, DAN KUALITAS PELAYANANTERHADAP KEPUTUSAN PEMBELIAN KARTU DIGITAL BY.U DI KOTA SAMARINDA - Ahmad Iqzal; Finnah Fourqoniah (JISOS: JURNAL ILMU SOSIAL, 2023)
In today's digital era, people can search for information to communicate with other people wherever they are just by using smartphone a sophisticated with a smartphone connected to the internet, it will make it easier for him to disseminate and obtain information, and it is also much more efficient in conducting communication interactions without any obstacles. Therefore, to access the internet requires a network produced by telecommunications companies. In responding to consumer demand for network services in communication, several telecommunication companies compete by innovating to make a product with various superior features. by.U was officially launched by Telkomsel on October 10, 2019. by.U is the first digital-based provider product in Indonesia that provides an end-to-end to meet telecommunication needs. This study aims to determine whether: price, brand image, and service quality affect purchasing decisions on by.U Digital Cards in Samarinda City. The population in this study are consumers who use or have purchased a by.U Digital Card in Samarinda City.sampling technique used was accidental sampling, the data was obtained by distributing questionnaires to 100 respondents. The data analysis technique in this study is descriptive analysis, classical assumption test and Multiple Linear Regression analysis using the SPSS Statistics 25 application program. The results show that: 1) price has no significant effect on purchasing decisions, because low prices are the source of most purchasing decisions. important, but the price factor is not a guarantee that a product has good quality. 2) brand image does not have a significant effect on purchasing decisions, because for consumers a good brand image may not necessarily make them want to buy or try the product, some consumers consider other things more, for example product or service quality, friend recommendations or according to their wishes. alone. 3) the quality of service has a significant effect on purchasing decisions, because the existence of quality services will encourage consumer purchasing decisions. In addition, quality service can also encourage consumers to forge strong bonds with the company. and 4) price, brand image, and service quality simultaneously affect purchasing decisions.